Visual limitations do not indicate poor quality of life: reflections by future eye care professionals. Issue 1 (2nd January 2022) - Lucas, Cherie; Nguyen, Vincent
ABSTRACT: This paper describes a study analysing eye care professional students' written reflections following their engagement with clients with low vision conditions. By embedding a reflective practice model (Schon's reflection-in-action and reflection-on-action ) within a higher education curriculum, students' assumptions and beliefs were challenged. Analysis of fifty-two reflective essays were analysed using the Braun and Clarke's 6-phase process for inductive thematic analysis. This generated three themes: (i) Students' perceptions that visual limitations do not necessarily equate to a poorer quality of life; (ii) Extrinsic and intrinsic influences affect patient care; and (iii) Eye care professionals' role expands to holistic care. An additional outcome of this study supports embedding reflective practice activities within the curriculum. By providing students with a platform to reflect and challenge their assumptions, may have the potential to enhance their understanding and improve future practice.